Da informação ao conhecimento :o jornalismo científico na contemporaneidade - Veras Júnior, José Soares de (2005)
The purpose of this dissertation is to analyze the actual nature of the Scientific Journalism, studying the historical facts from these informations segment, their matters production and the news industries that work with these specific niche of the contemporary journalism. It is taken into account the educational potential of the specialized journalism and it is considered the communication as a transdiciplinary science. To get into this point it was elected as an analyze category the Reception it Mediation Studies specially the north-americans theories besides the utilization also of the reportage concept to identify how to establish the epistemological relations between Communication and Education. Among the objectives of this dissertation are the investigation of the scientific character of the journalism; the analysis of the theoretical currents of Pedagogy that are based on the theory of Social Communication, as for example the Total Language and the analysis of the industrial and technological characteristics of the most important scientific and cultural magazines of Brazil, Northeast and Natal